Mri of finger pulleys at 7t—direct characterization of pulley ruptures in an ex vivo model - Heiß, Rafael; Librimir, Alexander; Lutter, Christoph; Janka, Rolf Matthias; Kuerten, Stefanie; Roemer, Frank; Nagel, Armin Michael; Uder, Michael; Bayer, Thomas (Diagnostics, 2021)
The aim of this study was to evaluate 7 Tesla (7T) magnetic resonance imaging (MRI) for direct visualization and specific characterization of the finger flexor pulleys A2, A3, and A4 before and after ex vivo pulley rupture. Thirty fingers of human cadavers were examined before and after pulley disruption with a 26 min clinical 7T pulse sequence protocol. Images were assessed by two experienced radiologists for the presence of pulley rupture. Injury characterization included definition of rupture location, morphology, and complications. Image quality was evaluated according to a 4-point Likert-type scale from “not evaluable” to “excellent”. Macroscopic preparations were used as the reference standard. Direct characterization of intact A2, A3, and A4 pulleys and the corresponding pulley lesions was possible in all cases. The rupture location was distributed equally at the radial, ulnar, and central parts of the pulleys. A dislocation and intercalation of the pulley stump between the flexor tendon and finger phalanges was observed as a complication in 62.5% of cases. The average Likert score for direct visualization of pulleys was 2.67 before rupture and 2.79 after rupture creation, demonstrating adequate image quality for routine application. 7T MRI enables a direct characterization of A2, A3, and A4 pulleys before and after artificial disruption, including the definition of rupture morphology and location as well as the detection of rupture complications. This promises a precise presurgical evaluation of pulley injuries and complicated pulley stump dislocations.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Climbing; Finger flexor pulleys; Imaging; Injury classification; Ultra-high-field MRI